Modeling the Nonlinearity of Sea Level Oscillations in the Malaysian Coastal Areas Using Machine Learning Algorithms - Lai V.; Ahmed A.N.; Malek M.A.; Afan H.A.; Ibrahim R.K.; El-Shafie A.; El-Shafie A. (MDPI, 2023)
coastal zone; design method; genetic algorithm; machine learning; prediction; sea level change; support vector machine; Malaysia; Pahang; Seribuat Archipelago; Tioman; West Malaysia